Meningkatkan Kemampuan Membaca Kelas 1 Pada SD Negeri Tarusan Danum Dengan Menggunakan PAKEM (Pembelajaran Yang Aktif, Kreatif, Efektif, Dan Menyenangkan) - Artatiana Artatiana (FKIP Universitas Palangka Raya, 2023)
This study aims to improve students' reading skills in the Indonesian language subject through the application of the PAKEM method (Active, Creative, Effective and Fun Learning) at SDN Tarusan Danum, Tewang Sagalang Garing District, Katingan Regency. Based on the results of observations in the class, it was found that there were students who could not read fluently. The number of students who still could not read fluently was 14 out of a total of 17 students. This Classroom Action Research (CAR) was conducted for two months using the PAKEM method in an effort to improve the reading skills of class I students at SDN Tarusan Danum. This research was conducted through four cycles where each cycle consisted of one meeting through several stages, namely planning, observing and reflecting. The data collection technique was carried out using observations at each meeting by observers and learning outcomes were taken from the value of the ability results (achieved or not the ability aspect indicators) of students in each cycle. The results of this study, in the first cycle was 48%, in the second cycle was 68%, in the third cycle was 79% and in the fourth cycle was 94%. The results obtained from the first, second, third and fourth cycles of this study show that using the PAKEM method in improving students' reading skills in the Indonesian subject experienced an average increase of 72%.